Flux surface identification by spatio-temporal coupling with partial mutual information analysis of electron cyclotron emission data. (10th November 2020) - Guerrero Arnaiz, J F; Dinklage, A; Pompe, B; Geiger, J; Hirsch, M; Höfel, U; Marushchenko, N; Turkin, Y; Wolf, R C; ,
Abstract: Fluctuations of electron cyclotron emission (ECE) signals are analyzed for differently heated Wendelstein 7-X plasmas. The fluctuations appear to travel predominantly on flux surfaces and are used as 'tracers' in multivariate time series. Different statistical techniques are assessed to reveal the coupling and information entropy-based coupling analysis are conducted. All these techniques provide evidence that the fluctuation analysis allows one to check the consistency of magneto-hydrodynamic (MHD) equilibrium calculations. Expanding the suite of techniques applied in fusion data analysis, partial mutual information (PMI) analysis is introduced. PMI generalizes traditional partial correlation (Frenzel and Pompe Phys. Rev. Lett. 99 204101) and also Schreiber's transfer entropy (Schreiber 2000 Phys. Rev. Lett. 85 461). The main additional capability of PMI is to allow one to discount for specific spurious data. Since PMI analysis allows one to study the effect of common drivers, the influence of the electron cyclotron resonance heating on the mutual dependencies of simultaneous ECE measurements was assessed. Additionally, MHD mode activity was found to be coupled in a limited volume in the plasma core for different plasmas. The study reveals an experimental test for equilibrium calculations and ECE radiation transport.